Influence of the Mixing Ways of Reactants on ZnO Morphology. (24th March 2013) - Yang, Lining; Xiang, Lan
Abstract : ZnO particles with various morphologies were synthesized by mixing ZnSO4 and NaOH solutions at 25°C followed by aging of the suspensions at 40–80°C for 2.0 h, keeping the initial molar ratio of Zn 2+ to OH − at 1 : 4. ZnO irregular plates were prepared by adding NaOH to ZnSO4 while ε -Zn(OH)2 rhombic particles were produced using the opposite mixing way. After aging of the slurries at 80°C for 2.0 h, the ZnO plates were kept stable while the ε -Zn(OH)2 rhombic particles were converted to ZnO whiskers with a length of 1.0–4.0 μ m and a diameter of 0.03–0.3 μ m. Thermodynamic analysis indicated that the formation of the Zn-bearing precipitates (ZnO or ε -Zn(OH)2 ) at room temperature was connected closely with the solution composition.